Foreign body removal in the thoracic esophagus by esophagotomy in a canine: Case report - Laverde, Néstor (2023)
The case of a 22-month-old female canine, Bernese Mountain breed, treated at the AsMeVet veterinary hospital in the city of Tunja, Colombia, diagnosed with partial esophageal obstruction is presented. The owner reported that the patient ate a pig bone the day before, of which she vomited several pieces, but she ate them again. However, from that time on she did not eat again but she drank water normally. On clinical examination, he is found to be depressed, dehydrated, and reluctant to eat. The chest X-ray revealed a radiopaque foreign body between the seventh and ninth rib. A left caudal lateral thoracotomy was performed to remove the bone by esophagotomy. The patient was medical discharged 72 hours after surgery.